Pengaruh Budaya Organisasi dan Motivasi terhadap Prestasi Karyawan melalui Kepuasan Kerja Sebagai Variabel Intervening di Saffah Konveksi Sukoharjo - Wibowo, Kurniawan Mukti; Kirana, , Kusuma Chandra; Subiyanto, Didik (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research to examine the effect of organizational culture and motivation on employee performance through job satisfaction as an intervening variable at Saffah Convection Sukoharjo. This research is quantitative with the sampling method being non-probability and the sampling technique using saturated sampling which takes 100% of the total population of Saffah Convection Sukoharjo employees, namely as many as 50 respondents. Data collection was carried out by distributing online questionnaires to respondents. Data were analyzed using the IBM SPSS Version 25 application. The results of this study indicated that the organizational culture variable (X1) had a positive and significant effect on job satisfaction (Z) with a value of 0.025. Then the motivation variable (X2) has a positive and significant effect on job satisfaction (Z) with a value of 0.003. In addition, the organizational culture variable (X1) has a positive and significant effect on employee performance (Y) with a value of 0.026. The motivation variable (X2) has a positive and significant effect on employee performance (Y) with a value of 0.015 and the job satisfaction variable (Z) has a positive and significant effect on employee performance (Y) with a value of 0.016. In addition, the results of the study also show that job satisfaction can act as an intervening variable for the influence of organizational culture and motivation on employee performance at the Saffah Convection of Sukoharjo. Keywords: Organizational Culture, Motivation, Job Satisfaction, Employee Performance